MORPHOLOGICAL CHANGES DURING THE DEVELOPMENT OF SOMATIC EMBRYOS OF SAGO (Metroxylon sagu Rottb.) - Kasi, Pauline D.; ., Sumaryono (Indonesian Agency for Agricultural Research and Development - MOA, 2007)
Development of somatic embryos of sago (Metroxylon saguRottb.) on agar-solidified medium are highly varied producingheterogeneous seedlings. Understanding of this phenomenon mayhelp in improving the cultural procedures and conditions of sagosomatic embryogenesis to obtain uniform seedlings in a largescale. This experiment was conducted at the laboratory for plantcell culture and micropropagation, Indonesian BiotechnologyResearch Institute for Estate Crops from January to March 2006to examine morphological changes i.e. color and developmentstages of sago during their somatic embryo development on anagar-solidified medium. Twenty single globular somatic embryosof sago with specific color (yellowish, greenish, and reddish)were cultured in a Petri dish supplemented with a solid medium.The medium was a micronutrients-modified MS (MMS) withhalf strength of macronutrients containing 0.01 mg l-1 ABA, 2mg l-1 kinetin, 20 g l-1 sucrose, 0.5 g l-1 activated charcoal, and2 g l-1 gelrite. Parameter observed was the percentage ofembryoâs number based on color and developmental stage. Theresult showed that at the end of 6-week culture passage, mostoriginally greenish (80.8%) and reddish (95.8%) embryosremained unchanged in their colors, whereas almost half of theoriginally yellowish embryos turned to greenish and only 30%remained yellowish. At the same time, single globular embryoshave changed gradually into the next developmental stages,although not all of the embryos were germinated. The initialcolor of embryo affected the rate of the developmental stagechanges. Yellowish and greenish globular embryos developedmore rapidly into cotyledon or germinant stages at 58% and55% respectively, in 6 weeks than the reddish ones (41%).Therefore, the yellowish and greenish embryos are the bestsources of material for in vitro mass propagation and syntheticseed production of sago.